A small-sized and stable 2D metal–organic framework: a functional nanoplatform for effective photodynamic therapy. Issue 45 (11th November 2019) - Gao, Zhiguo; Chen, Fanghui; Li, Yaojia; Zhang, Yu; Cheng, Kaiwu; An, Peijing; Sun, Baiwang
Abstract : A small-sized 2D metal–organic framework with remarkable ROS generation ability through enhanced intersystem crossing. Abstract : The efficiency of photosensitizers in tumor photodynamic therapy (PDT) often compromises their poor water solubility, low extinction coefficients, photobleaching, and dissatisfactory reactive oxygen species (ROS) generation efficiency. Herein, a nanoscale 2D metal–organic framework, Sm-H2 TCPP nanosheets, was first synthesized by Sm 3+ -driven coordination with a porphyrin derivative (tetrakis(4-carboxyphenyl)porphyrin (H2 TCPP)) for highly effective PDT of breast cancer. The prepared Sm-H2 TCPP possessed nanoplate morphology with ultrathin thickness at the sub-10 nm level and an ultrasmall plane size at the sub-100 nm level. Compared with free H2 TCPP, the prominent ROS generation capacity of the well-defined Sm-H2 TCPP nanosheets is mainly attributed to their improved physicochemical properties and the enhanced intersystem crossing caused by heavy Sm nodes. The significantly improved PDT efficacy of the Sm-H2 TCPP nanosheets was further investigated in vitro and in vivo based on the MCF-7 breast cancer model. It is envisaged that the Sm-H2 TCPP nanosheets will offer a new avenue for the development of a new class of potential PDT agents.